The Small Regulatory RNAs LhrC1–5 Contribute to the Response of Listeria monocytogenes to Heme Toxicity - dos Santos, Patrícia T.; Menendez-Gil, Pilar; Sabharwal, Dharmesh; Christensen, Jens-Henrik; Brunhede, Maja Z.; Lillebæk, Eva M. S.; Kallipolitis, Birgitte H. (Frontiers in Microbiology, 2018)
The LhrC family of small regulatory RNAs (sRNAs) is known to be induced when the foodborne pathogen Listeria monocytogenes is exposed to infection-relevant conditions, such as human blood. Here we demonstrate that excess heme, the core component of hemoglobin in blood, leads to a strong induction of the LhrC family members LhrC1-5. The heme-dependent activation of lhrC1-5 relies on the response regulator LisR, which is known to play a role in virulence and stress tolerance. Importantly, our studies revealed that LhrC1-5 and LisR contribute to the adaptation of L. monocytogenes to excess heme. Regarding the regulatory function of the sRNAs, we demonstrate that LhrC1-5 act to down-regulate the expression of known LhrC target genes under heme-rich conditions: oppA, tcsA and lapB, encoding surface exposed proteins with virulence functions. These genes were originally identified as targets for LhrC-mediated control under cell envelope stress conditions, suggesting a link between the response to heme toxicity and cell envelope stress in L. monocytogenes. We also investigated the role of LhrC1-5 in controlling the expression of genes involved in heme uptake and utilization: lmo2186 and lmo2185, encoding the heme-binding proteins Hbp1 and Hbp2, respectively, and lmo0484, encoding a heme oxygenase-like protein. Using in vitro binding assays, we demonstrated that the LhrC family member LhrC4 interacts with mRNAs encoded from lmo2186, lmo2185 and lmo0484. For lmo0484, we furthermore show that LhrC4 uses a CU-rich loop for basepairing to the AG-rich Shine-Dalgarno region of the mRNA. The presence of a link between the response to heme toxicity and cell envelope stress was further underlined by the observation that LhrC1-5 down-regulate the expression of lmo0484 in response to the cell wall-acting antibiotic cefuroxime. Collectively, this study suggests a role for the LisR-regulated sRNAs LhrC1-5 in a coordinated response to excess heme and cell envelope stress in L. monocytogenes.